Conservation Agriculture Improves Soil Quality, Crop Yield, and Incomes of Smallholder Farmers in North Western Ghana - Naab, Jesse B.; Mahama, George Y.; Yahaya, Iddrisu; Prasad, P. V. V. (Frontiers in Plant Science, 2017)
Conservation agriculture (CA) practices are being widely promoted in many areas in sub-Saharan Africa to recuperate degraded soils and improve ecosystem services. This study examined the effects of three tillage practices [conventional moldboard plowing (CT), hand hoeing (MT) and no-tillage (NT)], and three cropping systems [continuous maize, soybean-maize annual rotation and soybean/maize intercropping] on soil quality, crop productivity and profitability in researcher and farmer managed on-farm trials from 2010 to 2013 in northwestern Ghana. In the researcher managed mother trial the CA practices of no-tillage, residue retention and crop rotation/intercropping maintained higher soil organic carbon, and total soil N compared to conventional tillage practices after four years. Soil bulk density was higher under no-tillage than under CT soils in the researcher managed mother trails or farmers managed baby trials after four years. In the researcher managed mother trial, there was no significant difference between tillage systems or cropping systems in maize or soybean yields in the first three seasons. In the fourth season, crop rotation had the greatest impact on maize yields with CT maize following soybean increasing yields by 41% and 49% compared to MT and NT maize respectively. In the farmers’ managed trials, maize yield ranged from 520 – 2700 kg ha-1 and 300 – 2000 kg ha-1 for CT and NT respectively reflecting differences in experience of farmers. Averaged across farmers, CT cropping systems increased maize and soybean yield ranging from 23 to 39% compared with NT cropping systems. Partial budget analysis showed that the cost of producing maize or soybean is 20 – 29% cheaper with NT systems and gives higher returns to labor compared to CT practice. Benefit-to-cost ratios also show that NT cropping systems are more profitable than CT systems. We conclude that with time, implementation of CA practices involving NT, crop rotation, intercropping of maize and soybean along with crop residue retention presents a win-win scenario due to improved crop yield, increased economic return, and trends of increasing soil fertility. The biggest challenge however remains with producing enough biomass and retaining same on the field.